2023
DOI: 10.1037/hum0000245
|View full text |Cite
|
Sign up to set email alerts
|

When are the dogs coming back? Animal-assisted activities with men in residential substance abuse treatment.

Abstract: Recent research has demonstrated the many benefits of human-animal interaction through traditional modalities, such as service dogs and pets, to more recent initiatives designated as Animal-Assisted Interventions (AAIs). AAIs are quite varied ranging in setting-educational, therapeutic, residential; as well as process-group vs individual, and ongoing vs single dose. Even a single dose of Animal-Assisted Activities (AAAs) has been shown to provide relief from anxiety and stress. Individuals recovering from subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The researchers observed that the chickens made the farm visitors laugh, which left us wondering if the visitors made the chickens laugh as well. Scott and Kirnan (2023) introduce animal-assisted activities (AAA) to produce a significant reduction of anxiety in men in substance abuse recovery within residential facilities. The authors advocate for and provide step-by-step suggestions for facilities interested in incorporating AAAs into substance abuse treatment plans. Reciprocity and the healing relationship .…”
Section: This Special Issue On “Human–animal Relations”mentioning
confidence: 99%
“…The researchers observed that the chickens made the farm visitors laugh, which left us wondering if the visitors made the chickens laugh as well. Scott and Kirnan (2023) introduce animal-assisted activities (AAA) to produce a significant reduction of anxiety in men in substance abuse recovery within residential facilities. The authors advocate for and provide step-by-step suggestions for facilities interested in incorporating AAAs into substance abuse treatment plans. Reciprocity and the healing relationship .…”
Section: This Special Issue On “Human–animal Relations”mentioning
confidence: 99%